Improving Students' Interest in Learning Through Various Creative Methods at Madrasah Ibtida’iyah (Islamic Elementary School) PAS Baitul Qur'an Gontor Ponorogo - Aan Ariadi; Nurul Iman; Anip Dwi Saputro; Sigit Dwi Laksana (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2021)
One factor that greatly affects student learning outcomes is interest. Interest becomes a very important factor to make students pay attention, focus and be actively involved in the learning process. Teachers need to learn various ways to increase student interest in learning so that learning goals can be reached optimally. The problem formulation in this study is how students' interest, how the teacher in increasing student interest, and how the results of the teacher search in increase students' interest. The type of research conducted is research that uses qualitative methods. While the data collection techniques used are using observation, interviews, and documentation. In qualitative data analysis this analysis is carried out interactively and is carried out continuously until finished, so that the data is already saturated. Based on data analysis, the authors conclude: First, students' interest has a good enthusiasm to look at the theory of interest. Second, try the moral teacher in increasing student learning interest is Developing a learning plan to determine the method with the subject matter to be delivered. Third, the teacher's search results in increasing student interest responded well from students who moved the teacher in increasing focus or increasing students.